Total Knee Arthroplasty in Extra-Articular Knee Deformity Patients: A Review of the Surgical Techniques, Surgical Instruments and Prosthetic Designs - Rattanaprichavej, Piti (Naresuan University Journal: Science and Technology (NUJST); Vol 22 No 3 (2014): September-December 2014, 2014)
Total knee arthroplasty (TKA) is the gold standard procedure for the end-stage destructive arthropathy of the knee. TKA can relieve pain and restore knee function. The post-operative mechanical axis should be within a +/-3 degree of a neutral mechanical axis to ensure a good long-term result and maximize the longevity of TKA. Performing TKA in patients with ipsilateral extra-articular deformity is very challenging. Anatomy distortion, canal sclerosis, retained hardware and prior surgery in this patient group will increase the risk of prosthesis malposition and malalignment of the lower extremity, which may hinder the outcome and survival of TKA. Intra-articular correction technique is suitable when the coronal plane deformity less than 20 degree for femur and less than 30 degree for tibia. If intra-articular correction technique cannot correct the deformity, then extra-articular correction technique is indicate. Computer-assisted surgery (CAS) and Patient-specific instruments (PSIs) will be a good assistant by ignoring the anatomical distortion of patients. Well-planned preoperative planning combined with an appropriate surgical technique, proper surgical instruments and wisely chosen prosthesis design will reduce the risk of complications and thus maximize the outcome and longevity of TKA in patients with extra-articular deformity. Keywords: Total knee arthroplasty, TKA, extra-articular deformity TKA, intra-articular correction technique, extra-articular correction technique
Keywords: Total knee arthroplasty, TKA, extra-articular deformity TKA, intra-articular correction technique, extra-articular correction technique